2014
DOI: 10.13005/bpj/480
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Titanium Mini Plates in Management of Mandibular Fractures

Abstract: Over the years, the management of trauma has evolved from various forms of splinting circum mandibular wiring (R.J.Fonseca&R.V.Walker) extraoral pins, semi rigid fixation and trans-osseous wiring. This was followed by rigid fixation technique and more lately has given way to semi-rigid fixation with miniplates (Champy.M.et al) 3,10,11. The currently used conventional miniplates technique requires maxillomandibular fixation for a short period and unable to render three dimensional stability at the fracture site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Among the articles selected for the final review, 16 reported prospective studies [3][4][5]9,10,18,21,22,[26][27][28][29][30][31][32][33] , seven reported retrospective studies 8,17,[34][35][36][37][38] , and two reported case series 16,39 . Regarding the evaluation of quality, three studies presented a low risk of bias 10,31,32 , six a moderate risk [3][4][5]17,21,30 , and 16 a high risk 8,9,16,18,22,[26][27][28][29][33][34][35][36][37][38][39] (Table…”
Section: Resultsmentioning
confidence: 99%
“…Among the articles selected for the final review, 16 reported prospective studies [3][4][5]9,10,18,21,22,[26][27][28][29][30][31][32][33] , seven reported retrospective studies 8,17,[34][35][36][37][38] , and two reported case series 16,39 . Regarding the evaluation of quality, three studies presented a low risk of bias 10,31,32 , six a moderate risk [3][4][5]17,21,30 , and 16 a high risk 8,9,16,18,22,[26][27][28][29][33][34][35][36][37][38][39] (Table…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that 3D titanium miniplates were a viable option for the management of mandibular fractures with the advantages of placement through an intraoral approach, minimizing surgical period and trauma with the added advantage of simple techniques for adaptation to the bone. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Literature says the most universal etiological factor related to maxillofacial injuries is road traffic accident (RTA) which shows around 45.3% involvement [1]. Causes other than RTA include falls (42.6%), assaults (0.89%), sport injuries (2.2%), and gunshot wounds (0.89%) [2]. As the mandible shows more central position of face and secondly due to its obvious prominence it gets fractured more often [3].…”
Section: Introductionmentioning
confidence: 99%
“…Noticeable gaines of rigid fixation are short MMF period or even no MMF, mandibular function that gets early in incorporation, boost in patient happiness and quicker healing [7]. The main drawback in using routine miniplates technique is that it seems deficient tin providing three dimensional stability of the fractured segment, and that too require maxilla-mandibular fixation for a short period [2,4,8]. In recent years the most latest technique in treating maxilla-mandibular surgery is by the three dimensional (3-D) miniplates system, which is also a rigid fixation method [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation